Analisis Pengaruh Fluktuasi Muka Air Waduk terhadap Stabilitas Lereng Waduk Dengan Menggunakan Program Plaxis 2D - Wulandari, Paravita Sri; Tjandra, Daniel (Department of Civil Engineering, Diponegoro University, 2018)
Reservoir is needed as a source of water supply to the surrounding populations. The design of a reservoir needs to consider several aspects of soil embankment such as variations in water content and changes in shear soil shear strength and also the influence of water level in reservoir. The purpose of this research is to analyze these three aspects in the design of a reservoir. This research was begun by taking soil samples for embankment and conducting soil tests to obtain soil characteristics at the initial condition. The further laboratory tests were conducted to determine the effect of changes in water content on the shear strength of the soil. The variation of soil embankment characteristic was then modeled by Plaxis 2D program to obtain the effect of changes in soil embankment characteristic and fluctuation of the water level in the reservoir. The results showed that the increase in water content significantly decrease the shear strength of the soil. The changes of soil shear strength affect the pattern of slope failure and safety factor. In addition, the pattern and direction of the slope failure were also influenced by the water level of the reservoir.